Compressive strength and chloride resistance of self-compacting concrete containing high level fly ash and silica fume - Wongkeo W. (Elsevier Ltd, 2014)
The influence of high-calcium fly ash and silica fume as a binary and ternary blended cement on compressive strength and chloride resistance of self-compacting concrete (SCC) were investigated in this study. High-calcium fly ash (40-70%) and silica fume (0-10%) were used to replace part of cement at 50, 60 and 70. wt.%. Compressive strength, density, volume of permeable pore space (voids) and water absorption of SCC were investigated. The total charge passed in coulombs was assessed in order to determine chloride resistance of SCC. The results show that binary blended cement with high level fly ash generally reduced the compressive strength of SCC at all test ages (3, 7, 28 and 90. days). However, ternary blended cement with fly ash and silica fume gained higher compressive strength after 7. days when compared to binary blended fly ash cement at the same replacement level. The compressive strength more than 60. MPa (high strength concrete) can be obtained when using high-calcium fly ash and silica fume as ternary blended cement. Fly ash decreased the charge passed of SCC and tends to decrease with increasing fly ash content, although the volume of permeable pore space (voids) and water absorption of SCC were increased. In addition when compared to binary blended cement at the same replacement level, the charge passed of SCC that containing ternary blended cement was lower than binary blended cement with fly ash only. This indicated that fly ash and silica fume can improve chloride resistance of SCC at high volume content of Portland cement replacement.